Gene regulatory network analysis of silver birch reveals the ancestral state of secondary cell wall biosynthesis in core eudicots - Ilievska, Maja; Chong, Sun Li; Lim, Kean Jin; Immanen, Juha; Nieminen, Kaisa; Maaheimo, Hannu; Helariutta, Yrjö; Wurman-Rodrich, Joel; Dupree, Paul; Ord, James; Tenkanen, Maija; Salojärvi, Jarkko (John Wiley & Sons, 2025)
The compact genome and lack of recent whole-genome multiplication (WGM) events make the boreal pioneer tree silver birch (Betula pendula) a promising model for primary and secondary cell wall (PCW and SCW) regulation in forest trees. Here, we constructed regulatory networks through combined co-expression and promoter motif analysis and carried out a tissue-wide analysis of xylan using mass spectrometry. Analyses confirm the evolutionarily conserved model of superimposed layers of regulation and suggest a relatively simple ancestral state still retained in birch. Multispecies network analysis, including birch, poplar, and eucalyptus, identified conserved regulatory interactions, highlighting lignin biosynthesis as least conserved. The SCW biosynthesis co-expression module was enriched with WGM duplicates. While regulator genes were under positive selection, others evolved under relaxed purifying selection, possibly linked with diversification, as indicated by expression and regulatory motif differences. Xylan composition varied between PCW and SCW, revealing unique acetylation patterns. PCW xylan biosynthesis genes showed distinct expression and regulatory motifs, with a novel acetyl transferase potentially involved. This work highlights birch as a valuable model for understanding wood formation, vascular development, and cell wall composition in eudicots.
Keywords: transcriptomics; Gene regulation; genome evolution; Betula pendula (silver birch); wood development